Advances in Neural Network Research and Applications - Zeng, Zhigang; Wang, Jun.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book is a part of the Proceedings of the Seventh International Symposium on Neural Networks (ISNN 2010), held on June 6-9, 2010 in Shanghai, China. ISNN 2010 received numerous submissions from about thousands of authors in about 40 countries and regions across six continents . Based on the rigorous peer-reviews by the program committee members and the reviewers, 108 high-quality papers were selected for publications in Lecture Notes in Electrical Engineering (LNEE) Proceedings. These papers cover all major topics of the engineering designs and applications of neural network research. In addition to the contributed papers, the ISNN 2010 technical program included four plenary speeches by Andrzej Cichocki (RIKEN Brain Science Institute, Japan), Chin-Teng Lin (National Chiao Tung University, Taiwan), DeLiang Wang (Ohio State University, USA), Gary G. Yen (Oklahoma State University, USA).
Prediction and Forecasting -- Fuzzy Neural Networks -- Optimization and Planning -- Pattern Recognition -- Signal and Image Processing -- Robotics and Control -- Transportation Systems -- Industrial Applications -- Real-World Applications.
Keywords: Engineering; Artificial intelligence; Production of electric energy or power; Engineering; Power Electronics, Electrical Machines and Networks; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Control